Common Atrial Fibrillation Risk Alleles at 4q25 Predict Recurrence after Catheter-based Atrial Fibrillation Ablation - Shoemaker, M. Benjamin (2012)
BACKGROUND: Common single nucleotide polymorphisms (SNPs) at chromosome 4q25 (rs2200733, rs10033464) are associated with both lone and typical AF. Risk alleles at 4q25 have recently been shown to predict recurrence of AF after ablation in a population of predominately lone AF, but lone AF represents only 5–30% of AF cases. OBJECTIVE: To test the hypothesis that 4q25 AF risk alleles can predict response to AF ablation in the majority of AF cases. METHODS: Patients enrolled in the Vanderbilt AF Registry underwent 378 catheter-based AF ablations (median age 60 years, 71% male, 89% typical AF) between 2004 and 2011. The primary endpoint was time to recurrence of any non-sinus atrial tachyarrhythmia (atrial tachycardia, atrial flutter, or AF; [AT/AF]). RESULTS: Two-hundred AT/AF recurrences (53%) were observed. In multivariable analysis, the rs2200733 risk allele predicted a 24% shorter recurrence-free time (survival time ratio 0.76 95% confidence interval [CI] 0.6–0.95, P=0.016) compared with wild-type. The heterozygous haplotype demonstrated a 21% shorter recurrence-free time (survival time ratio = 0.79, 95% CI 0.62–0.99) and the homozygous risk allele carriers a 39% shorter recurrence-free time (survival time ratio = 0.61, 95% CI 0.37–1.0) (P=0.037). CONCLUSION: Risk alleles at the 4q25 loci predict impaired clinical response to AF ablation in a population of predominately typical AF patients. Our findings suggest the rs2200733 polymorphism may hold promise as an as an objectively measured patient characteristic that can used as a clinical tool for selection of patients for AF ablation.